Impact of external accreditation on students’ performance: Insights from a full accreditation cycle - Shuliweeh Alenezi; Ayman Al-Eadhy; Rana Barasain; Trad S. AlWakeel; Abdullah AlEidan; Hadeel N. Abohumid (Heliyon, 2023)
Background: The process of external academic accreditation involves quality control and auditing measures that focus on the design, delivery, and outcomes of education. It is a demanding and disruptive process in terms of effort, time, money, and human resources. Nevertheless, the extent to which external quality assurance and accreditation procedures affect students’ performance at the end of the learning cycle has not been well studied thus far. Methods: A retrospective quantitative secondary data analysis was conducted in The King Saud University (KSU) undergraduate medical program, with a before–after comparison research design to assess the impact of external accreditation on students’ mean grade scores during an accreditation cycle. Results: Overall, the data pertaining to 1090 students who attended 32,677 examination encounters were included in the analysis. The pre- and post-accreditation analysis revealed a statistically significant improvement in the students' mean scores—80 ± 9 (pre) versus 87 ± 11 (post), with a p-value of (p = 0.003) and a Cohen's d value of 0.591. On the other hand, there was no statistically significant difference in the students' mean passing percentages—96 ± 5 (pre) versus 96 ± 9 (post), with a p-value of (p = 0.815) and a Cohen's d value of 0.043. Conclusion: The actions involved in the planning phase and the journey through the self-study evaluation not only verify the program's competencies but also functioned as critical boosters for quality improvement processes and, hence, students' learning experiences.